Pre-Employment Card (Kartu Prakerja) In The Middle Of A Pandemic Review From The Concept Of Justice And Welfare - Risma Dewi Hermawan; Aris Prio Agus Santoso; Gempar Putra (Activa Yuris: Jurnal Hukum, 2021)
The Covid 19 pandemic that attacked the industrial world of the Indonesian which resulted in the termination of employment by several companies so that the government had implemented policies including by issuing the Pre-Employment Card (Kartu Prakerja) Program to overcome unemployment and create welfare and social justice, but in the practice there are still people who have not received a pre-employment card. The problem in this research is how to implement the pre-employment card in terms of the concept of welfare and justice. The research uses a statute approach method. The research focuses more on library data, namely research carried out on secondary data which includes Indonesia Constitution, the 5th principle of the Pancasila, namely "Social Justice for All Indonesian People", Presidential Decree No. 36 of 2020 "The Pre-Employment Card Program is a work competency development program aimed at job seekers, workers/laborers who have been laid off, and/or who need to increase their competence", Government Regulation No. 39 of 2012 "Social Security is a scheme institutionalized to ensure that all people can fulfill their basic needs for a decent life”. The results of the study prove that the government has provided funds for the pre-employment card program to help workers solve economic problems due to layoffs, but during the pandemic the pre-employment card policy to restore employee health has not been effective with the most recipients in West Java 16%, then DKI Jakarta (10%)), followed by East Java (9.8%). Meanwhile, the provinces with the lowest recipients were West Papua (0.08%), then Gorontalo (0.37%), and Papua (0.46%)